PENGEMBANGAN GAME EDUKASI “PUTRA DHAMMA” SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN PENDIDIKAN AGAMA BUDDHA - Irawan, Deny Sigit; Parsiyono, Parsiyono; Setyaningsih, Setyaningsih (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2018)
This research was done due to the lack of research on the learning media used in the Buddhism, and the manners related to the field of information and technology in the state Junior High School 1 Getasan, as well as the learning media in used at “PUTRA DHAMMA” educational game on the subject of Buddhist education. This research attempted to develop educational games “PUTRA DHAMMA” and get to know the feasibility of the response, as well as the students’ development in using the educational game “PUTRA DHAMMA” as a medium of learning to support the Buddhism and manners for students class VII state Junior High School 1 Getasan. The research was a research and development (R & D) using the PPE (planning, production, evaluation) model. The stages in the development of education games “PUTRA DHAMMA” consisted of three stages, namely: (1) planning or design; (2) production; and (3) evaluation. At the evaluation stage the validation on educational games “PUTRA DHAMMA” by experts on the media and the material, and teachers of Buddhism was performed. Educational games “PUTRA DHAMMA” were then tried out on 20 students of classes VII and VIII state Junior High School 1 Getasan. Data collection techniques were done through interviews, observation, and questionnaire. The data obtained from the questionnaire were then analyzed in qualitative and quantitative descriptive methods. The research results show that the rate of the feasibility of the educational games of “PUTRA DHAMMA” as a supporting medium of learning based on educational games are as follows: (a) assessment of the feasibility from media experts scores the average of 4.50 with the percentage of the feasibility of 89% in the category of very feasible; (b) assessment of the feasibility from expert of the of material received the avarage score of 3.79 with the feasibility 76% in the category of feasible; (c) assessment of the feasibility by the practitioner received the average score of 4.62 with the feasibility of 93% in the category of very reasonable. The assessment results from the students on the education games “PUTRA DHAMMA” are feasible with the average of 4.56 with the percentage feasibility of 91%. Thus the educational games “PUTRA DHAMMA” are worth to be used as a medium supporting the learning of Buddhist education class VII in State Junior High School 1 Getasan.